TERMINATION OF WAHDATUL WUJUD IN ISLAMIC CIVILIZATION IN ACEH: CRITICAL ANALYSIS OF ITHAF AD-DHAKI, THE WORKS OF IBRAHIM KURANI - Ismail Fahmi Arrauf Nasution (LPPM IAIN Kudus, 2017)
Wahdatul Wujud or Unity of Being is a sufi doctrine that is in accordance with the well-known, inclusive and permissive views of the people of Nusantara. The teaching has proven to be an important part in realizing the peaceful and harmonious civilization of the Islamic archipelago. Unfortunately when orthodox theology doctrines which nuanced exclusive and radical dominated the Muslim intellectual discourse of archipelago, the doctrine of Wahdatul Wujud become excluded and even terminated from the stage of Islamic intellectualism of archipelago. This paper wants to evaluate critically the work of Ibrahim Kurani, Ithaf ad-Dhaki bi Shahr at-Tuhfah al-Mursalah ila an-Nabi which was written intentionally to explain the papers of Muhammad Fadhullah al-Burhanpuri entitled at-Tuhfah al-Mursalah ila an-Nabi Which discusses the teachings of Wahdatul Wujud that had been spread in the archipelago. This Ibrahim Kurani’s works is necessasry to be evaluated though it is generally accepted as the synthesis of Wahdatul Wujud according to orthodox theology, but factually it has a very significant role in reducing this doctrine so that Wahdatul Wujud becomes a foreign doctrine in the archipelago. In this study the authors found some epistemological and academic error committed by Ibrahim Kurani to the doctrine of Wahdatul Wujud in his book. The author expects Wahdatul Wujud could be revived in scientific and academic discourse as a solution to counter the teachings of exclusive and radical Islam in order to realize a peaceful and democratic Islam as had happened in the history of Islamic civilization in archipelago.